Arctic rain on snow events: bridging observations to understand environmental and livelihood impacts. (6th October 2021) - Serreze, Mark C; Gustafson, Julia; Barrett, Andrew P; Druckenmiller, Matthew L; Fox, Shari; Voveris, Jessica; Stroeve, Julienne; Sheffield, Betsy; Forbes, Bruce C; Rasmus, Sirpa; Laptander, Roza; Brook, Mike; et al.
Abstract: When rain falls on an existing cover of snow, followed by low temperatures, or falls as freezing rain, it can leave a hard crust. These Arctic rain on snow (ROS) events can profoundly influence the environment and in turn, human livelihoods. Impacts can be immediate (e.g. on human travel, herding, or harvesting) or evolve or accumulate, leading to massive starvation-induced die-offs of reindeer, caribou, and musk oxen, for example. We provide here a review and synthesis of Arctic ROS events and their impacts, addressing human-environment relationships, meteorological conditions associated with ROS events, and challenges in their detection. From our assessment of the state of the science, we conclude that while (a) systematic detection of ROS events, their intensity, and trends across the Arctic region can be approached by combining data from satellite remote sensing, atmospheric reanalyses, and meteorological station records; (b) obtaining knowledge and information most germane to impacts, such as the thickness of ice layers, how ice layers form within a snowpack, and antecedent conditions that can amplify impacts, necessitates collaboration and knowledge co-production with community members and indigenous knowledge-holders.